Assessment of the Imperfections for Plate Buckling of Unstiffened Plates. Issue 2 (1st September 2021) - Schönfeld, Larissa; Naujoks, Bernd; Ludwig, Christian
Abstract: In this study different approaches and combinations of imperfections using GMNIA of unstiffened plates are examined. The imperfections have a crucial influence for the determination of the load bearing capacity of thin plates. According to EN 1993‐1‐5 Annex C, when using GMNIA, the user can choose between equivalent geometric imperfections and a combination of the geometrical and the structural imperfections. The exact influence of the individual imperfections and their combination on the load bearing behavior has not been conclusive clarified. Furthermore, EN 1993‐1‐5 Annex C does not recommend a suitable residual stress model. This study aims to compare the ultimate loads due to compression loading using different imperfection approaches. Ten different combinations are investigated by using GMNIA. The results show that for larger plate slenderness, many of the ultimate loads are above the Winter‐Curve. The influence of the structural imperfections on the ultimate load is higher than the influence of the geometrical imperfections. An appropriate residual stress model is recommended. The geometrical imperfections should be given as a function of the plate slenderness.